Functions of double‐negative B cells in autoimmune diseases, infections, and cancers - Michael King Yung Chung; Lanqi Gong; Dora Lai‐Wan Kwong; Victor Ho‐Fun Lee; Ann Wing‐Mui Lee; Xin‐Yuan Guan; Ngar‐Woon Kam; Wei Dai (EMBO Molecular Medicine)
Abstract Most mature B cells can be divided into four subtypes based on the expression of the surface markers IgD and CD27: IgD+CD27− naïve B cells, IgD+CD27+ unswitched memory B cells, IgD−CD27+ switched memory B cells, and IgD−CD27− double‐negative (DN) B cells. Despite their small population size in normal peripheral blood, DN B cells play integral roles in various diseases. For example, they generate autoimmunity in autoimmune conditions, while these cells may generate both autoimmune and antipathogenic responses in COVID‐19, or act in a purely antipathogenic capacity in malaria. Recently, DN B cells have been identified in nasopharyngeal carcinoma and non‐small‐cell lung cancers, where they may play an immunosuppressive role. The distinct functions that DN B cells play in different diseases suggest that they are a heterogeneous B‐cell population. Therefore, further study of the mechanisms underlying the involvement of DN B cells in these diseases is essential for understanding their pathogenesis and the development of therapeutic strategies. Further research is thus warranted to characterize the DN B‐cell population in detail.